Clinical and Radiographic Evaluation of Early Loaded Maxillary Anterior Single-Tooth Bone-Level Implants - KAHRAMANOĞLU, ERKUT; ÖZKAN, YASEMİN; ÖZKAN, YAŞAR (QUINTESSENCE PUBLISHING CO INC, 2014)
Purpose: The aim of this study was to evaluate the clinical and radiographic outcomes of early loaded platform-switched implants in the anterior maxilla. Materials and Methods: In this study, patients were treated with implants that supported all-ceramic single-tooth crowns and were followed for 2 to 4 years. Implants were evaluated on the basis of clinical and radiographic parameters, including Plaque Index, Sulcus Bleeding Index, peri-implant probing depths (PDs), Papilla Index, soft tissue recession, and marginal bone levels. Statistical analyses were performed. Results: Fifty-five implants were placed in 47 patients. At the recall examinations, all implants had successfully integrated, demonstrating healthy peri-implant soft tissues as documented by standard clinical parameters. At the time of recall, 7 implants had been followed for 4 years, 30 implants for 3 years, and 18 implants for 2 years. Plaque accumulation scores of 2 and 3 were not noted at any point during the study. At baseline, the mean PD was 2.1 +/- 0.6 mm, at 2 years it was 2.2 +/- 0.6 mm, at 3 years it was 2.2 +/- 0.6 mm, and at 4 years (7 implants), the mean PD was 1.9 +/- 0.4 mm. There were no statistically significant differences between time intervals. Complete papilla fill was seen for 49 implants. All implants showed less than 0.5 mm of marginal bone loss; mean bone loss at the time of final recall was 0.12 +/- 0.22 mm. Seven implants showed an increase in the level of bone contact. There were no statistically significant differences over time. Conclusion: Bone-level implants with a platform-switched design are a successful treatment modality for anterior single-tooth implants.
Keywords: anterior implant; bone-level implant; clinical study; dental implants; radiographic outcome; SOFT-TISSUE; AESTHETIC ZONE; IMMEDIATE; CRITERIA; HARD; NECK